1974
DOI: 10.1136/vr.95.2.34
|View full text |Cite
|
Sign up to set email alerts
|

Strongylus vulgaris infection in the horse

J. Duncan

Abstract: Chapter 1 The Development of a Technique for the Isolation and Maintenance of a Monospecific Infection of Strongylus vulgaris in the Horse 21 Chapter 2 The Life Cycle of Strongylus vulgaris in the Horse , 29 Chapter 3 The Pathogenesis of Experimental Strongylus vulgaris Infection in the Horse 46 Chapter 4 Field Studies on the Epidemiology of Mixed Strongyle Infection in the Horse 69 Chapter 5 Immunity to Strongylus vulgaris 93 References 113 Appendices 117 H. METEOROLOGICAL DATA The meteorological information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
(18 reference statements)
2
12
0
1
Order By: Relevance
“…The results of this study support the view of Duncan (1974b) that not all horses which suffer arterial damage show clinical signs. Many of the horses slaughtered during the present study were in apparent good health, in spite of the occurrence of verminous arteritis.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study support the view of Duncan (1974b) that not all horses which suffer arterial damage show clinical signs. Many of the horses slaughtered during the present study were in apparent good health, in spite of the occurrence of verminous arteritis.…”
Section: Discussionsupporting
confidence: 89%
“…However, aneurisms of the cranial mesenteric artery were not noticed in the material processed in this investigation. The arterial wall was thickened in variable percentages in all examined horses, which is consistent with many authors (Duncan, 1974;Radostis et al, 1994;Maxie and Robinson, 2007) which have the opinion that an aneurism is not a change related to verminous arteritis of the cranial mesenteric artery. Contrary to them other authors state that aneurisms are a regular change related to this disease (Forenbacher, 1983;Klei et al, 1990;Rooney and Robertson, 1996).…”
Section: Immunohistochemical Findingssupporting
confidence: 87%
“…The arterial wall is thickened (Radostis et al, 1994;Maxie and Robinson, 2007). According to one group of authors (Duncan, 1974;Maxie and Robinson, 2007) aneurisms are not a part of verminous arteritis and the common finding within this disease is thickening of the arterial wall. Contrary to them some authors are of the opinion that aneurisms are a regular finding within verminous arteritis (Forenbacher, 1983;Klei et al, 1990), while there are some authors which are of the opinion that aneurisms can be a finding, but not on a regular bases (Rooney and Robertson, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…But this does not necessarily mean that the parasite caused the disease in each case, as most horses without colic would also have been infected. Although experimental infections have shown that S. vulgaris is a parasite of high pathogenic potential (Duncan 1974; Duncan and Pirie 1975), we are not aware of any studies that have specifically evaluated the role of S. vulgaris in colic. Nevertheless, in the 1960s and 1970s S. vulgaris was recognised as an important cause of colic and was the primary target of parasite control programmes.…”
Section: A Shift In Emphasis: the Downfall Of Strongylus Vulgaris Andmentioning
confidence: 99%